EFL Student’s Perception of Teachers’ Hybrid Teaching Style: A Case Study - Salsa Rinata Dwi Marcelina; Luna Wang (Journal of Applied Linguistics and English Education, 2024)
This study aims to determine student perceptions of lecturers' teaching styles regarding hybrid learning. Because students' perceptions of how to teach lecturers towards hybrid learning currently are, of course, many differences that object over there are known to students, With this research, learn how to teach lecturers using contemporary media that oppose over there current exist right in addition to promising to do in addition to also in various ways. Sources of data from students' perceptions of hybrid teaching style; the writer collected data by interview; the writer interviewed 10 students of Universitas PGRIi Adi Buana Surabaya; however, only 5 students could participate in the interview. Data collection uses documentation techniques by making conversation transcripts. In addition, data were analyzed using reduction analysis in addition to interpretation. The results of this object over here study state that objects over there in the teaching style of lecturers in hybrid learning, it currently exists tremendously important to use media technology well, in addition to teachers now are also good at using media so that object over there students better understand the teacher's teaching style, in addition to teachers must also monitor students properly during hybrid learning.